How an emission trading system affects carbon emissions? Evidence from the urban agglomeration in the Middle Reaches of the Yangtze River, China - Jiayu Liu; Feng Xu; Yan Lv (Ecological Indicators, 2024)
The emission trading system (ETS) is one of the important policy instruments that help to achieve the “double carbon” goals, however, how the ETS affects the carbon emissions for an urban agglomeration remains uncertain. This study aims to explore the ETS’s impacts to carbon emission intensity (CEI) in Urban Agglomeration in the Middle Reaches of the Yangtze River (UAMRYR) of China during 2006–2018. By using the Difference-in-Differences (DID) model, the positive effects of ETS to CEI reduction were confirmed, and the robustness of findings were proved via the parallel trend test, placebo test, and propensity score matching DID (PSM-DID) method. This study also recognized two mediation impacting paths, which were economic intensity improvement and green technology innovation, and provided the evidence that the ETS could further reduce the CEI through improving the economic intensity as well as the green technology innovation. Furthermore, the study investigated the heterogeneous impacts from ETS by dividing the cities within the agglomeration into different orientations. The ETS performed better in the edge cities, and the same phenomenon occurred when considering the mediation effect from economic intensity. Policy recommendations about ETS were also provided.